Rheumatic Myocarditis: A Poorly Recognized Etiology of Left Ventricular Dysfunction in Valvular Heart Disease Patients - Rosa, Vitor Emer Egypto; Lopes, Mariana Pezzute; Spina, Guilherme Sobreira; Soares Junior, Jose; Salazar, David; Romero, Cristhian Espinoza; Lottenberg, Marcos Pita; de Santis, Antonio; Pires, Lucas José Neves Tachotti; Gonçalves, Luis Fernando Tonello; Fernandes, Joao Ricardo Cordeiro; Sampaio, Roney Orismar; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Heart failure occurs in ~10% of patients with acute rheumatic fever (RF), and several studies have shown that cardiac decompensation in RF results primarily from valvular disease and is not due to primary myocarditis. However, the literature on this topic is scarce, and a recent case series has shown that recurrent RF can cause ventricular dysfunction even in the absence of valvular heart disease. Methods: The present study evaluated the clinical, laboratory and imaging characteristics of 25 consecutive patients with a clinical diagnosis of myocarditis confirmed by 18F-FDG PET/CT or gallium-67 cardiac scintigraphy and RF reactivation according to the revised Jones Criteria. Patients underwent three sequential echocardiograms at (1) baseline, (2) during myocarditis and (3) post corticosteroid treatment. Patients were divided according to the presence (Group 1) or absence (Group 2) of reduced left ventricular ejection fraction (LVEF) during myocarditis episodes. Results: The median age was 42 (17–51) years, 64% of patients were older than 40 years, and 64% were women. Between Group 1 (n = 16) and in Group 2 (n = 9), there were no demographic, echocardiographic or laboratory differences except for NYHA III/IV heart failure (Group 1: 100.0% vs. Group 2: 50.0%; p = 0.012) and LVEF (30 [25–37] vs. 56 [49–62]%, respectively; p < 0.001), as expected. Group 1 patients showed a significant reduction in LVEF during carditis with further improvement after treatment. There was no correlation between LVEF and valvular dysfunction during myocarditis. Among all patients, 19 (76%) underwent 18F-FDG PET/CT, with a positive scan in 68.4%, and 21 (84%) underwent gallium-67 cardiac scintigraphy, with positive uptake in 95.2%, there was no difference between these groups. Conclusion: Myocarditis due to rheumatic fever reactivation can cause left ventricular dysfunction despite valvular disease, and it is reversible after corticosteroid treatment.